Peran Transportasi Laut dalam Mendukung Pemenuhan Barang Logistik Melalui Kantor Unit Penyelenggara Pelabuhan Kelas II Timika - Terianus Demena; Wening Nalurita (Indonesian Maritime Researchers and Lecturers, 2025)
The objectives of this study are: To determine the role of sea transportation in supporting the fulfillment of logistics needs through Timika Regency. To determine the strategy for developing sea transportation in supporting the fulfillment of logistics needs in Timika Regency. Research Objectives: 1) to determine the role of sea transportation in supporting the fulfillment of logistics needs through Timika Regency. 2) To determine the development of sea transportation in supporting the fulfillment of logistics needs through Timika Regency. The research method used is a qualitative descriptive research method. The research was conducted at the UPP Office and the Class II Timika Papua Tengah Port Authority. The research was conducted from March to June. The data collection techniques used were observation, documents, interviews. Research results: Efforts made by the UPP Office to improve ship safety at Timika Port 1) online inspection of ship documents and ship physicals 2) a. Opening access to isolated, remote, underdeveloped, and border areas to encourage increased local production and overcome disparities between regions. b. Connecting relatively underdeveloped inland areas with more advanced trade and government service centers. c. Establishing functional linkages between production areas and collection and distribution centers.